2012
DOI: 10.1172/jci45851
|View full text |Cite
|
Sign up to set email alerts
|

CD19 is a major B cell receptor–independent activator of MYC-driven B-lymphomagenesis

Abstract: PAX5, a B cell-specific transcription factor, is overexpressed through chromosomal translocations in a subset of B cell lymphomas. Previously, we had shown that activation of immunoreceptor tyrosine-based activation motif (ITAM) proteins and B cell receptor (BCR) signaling by PAX5 contributes to B-lymphomagenesis. However, the effect of PAX5 on other oncogenic transcription factor-controlled pathways is unknown. Using a MYC-induced murine lymphoma model as well as MYC-transformed human B cell lines, we found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
78
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 73 publications
9
78
0
Order By: Relevance
“…This link was strengthened by the observation that sIgM stimulation enhanced both CD19 surface expression and responsiveness. These data are in line with a recent study that established a linkage between the levels of CD19 expression and lymphoma progression (43). Ag stimulation is considered to be a key mediator in the development and progression of LPD (45).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This link was strengthened by the observation that sIgM stimulation enhanced both CD19 surface expression and responsiveness. These data are in line with a recent study that established a linkage between the levels of CD19 expression and lymphoma progression (43). Ag stimulation is considered to be a key mediator in the development and progression of LPD (45).…”
Section: Discussionsupporting
confidence: 90%
“…Further support for the existence of two modes of signaling via the BCR can be found in the observation that the levels of the activation marker CD86 were elevated in a similar manner both in the CD19-N and CD19-R cells in response to sIgM stimulation, but only the latter were able to aggregate in response to CD19 engagement. Interestingly, dissociated signaling between CD19 and other components of the BCR is supported by a recent study in B cell lymphomas (43). CD19 is able to provoke both Akt phosphorylation and cellular aggregation.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In this case, the CAR was created against CD19, which is found on the surface of normal and malignant B cells and is a popular target for gene therapy treatments against B-cell cancers. In addition it has been suggested that CD19 causes the upregulation of the MYC oncoprotein through the PAX5 transcription factor [7]. In this study, 11 patients received the T cells, all had shown multiple relapses of acute lymphoblastic leukemia (ALL; n = 4) or B-cell lymphoma (n = 7) after autologous (n = 3), allogenic (n = 3) or cord blood (n = 1) hematopoietic stem cell transplantation.…”
Section: News and Views Conference Scenementioning
confidence: 93%
“…Co-aggregate B-cell receptor and CD19/CD21 co-receptors are required for the survival of both resting and cycling B cells by regulating the cellular accumulation of the anti-apoptotic protein Bcl-2. 16,17 Additionally the B-cell receptor, by stabilizing the amount and activity of the oncoprotein c-Myc, 18,19 might facilitate B-cell lymphomagenesis through the CD19/RAS/ERK pathway, which can promote the expression of anti-apoptotic proteins. 19,20 Indeed, previous experimental data acquired through the use of Eμ-Myc transgenic mice demonstrated that the c-Myc/ERK/CD19 feedback signaling loop is important for the malignant transformation of B cells and in determining the severity of lymphomas.…”
Section: Introductionmentioning
confidence: 99%